A healthy lifestyle of the diabetic sufferer to avoid the risk of complications: Literature Review - Nini Asri Rahmayunita; Hamsu Kadriyan; Eka Arie Yuliyani (Jurnal Biologi Tropis, 2023)
Diabetes Mellitus (DM) is a chronic disease with high blood sugar levels in the blood. DM can cause complications of various diseases because the body can not use blood sugar in the blood cannot be used. The number of DM sufferers, both in the world and in Indonesia, continues to increase from time to time, so this disease is a scourge for everyone. Writing this paper aims to discuss the healthy lifestyle of diabetics to avoid the risk of complications. The most severe disorder of this disease is a chronic metabolic disorder because the pancreas does not produce enough insulin hormone, which has the principal role in regulating and controlling glucose metabolism into energy. Over time, diabetes can interfere with the function of human organs. For example, some organs work improperly, and some should be amputated. One of the most effective efforts to keep blood sugar levels stable is dietary compliance in people with diabetes mellitus has role function. The impact of dietary regulation is maintaining normal-body weight, reducing systolic and diastolic blood pressure, lowering blood glucose levels, improving lipid profiles, increasing insulin receptor sensitivity, and improving the blood coagulation system. This disease requires continuous medical care by carrying out independent health management in patients to prevent acute complications and reduce the risk of long-term complications. It is principal to adopt a healthy lifestyle for diabetic patients in a frame to anticipate the risk of complications.